Assessment of Seasonal Variation in Heavy Metal Status of a Lotic Ecosystem in Federal Capital Territory, Abuja, North Central Nigeria - Adano, Aminu Ja’afar; Marcus, Nengak Danjuma; Magaji, Joshua Ibrahim; Opaluwa, Obaje Daniel (Makara Journal of Science, 2023)
The concentrations of Cu, Zn, Fe, Cd, Co, Cr, and Mn and their seasonal variations in water samples from the Wupa River, Abuja, Nigeria, were studied through the atomic absorption spectrophotometric method to determine the suitability of the water for domestic usage and identify potential sources of contamination. Sixty samples were collected during both dry and wet seasons. The respective metal concentrations (in mg/dm3) in the dry and wet seasons were as follows: Cu (0.023 ± 0.022, 0.023 ± 0.026), Zn (0.104 ± 0.039, 0.158 ± 0.085), Fe (0.350 ± 0.097, 0.3630.103), Cd (not detectable), Co (not detectable), Cr (0.003 ± 0.003, 0.004 ± 0.004), and Mn (0.120 ± 0.132, 0.110 ± 0.099). Among these metals, Cu, Zn, Cr, and Mn occurred in concentrations below the tolerable limits recommended by Nigeria Standard for Drinking Water Quality and WHO, whereas Fe exceeded these limits, and Cd and Co were not detectable. The calculated heavy metal pollution index values (68.22 in the dry season and 63.78 in the wet season) were lower than the critical value (100), indicating low pollution levels in both seasons. The metal index values for both seasons (1.50 for the dry season and 1.55 for the wet season) suggest that the water from the Wupa River was slightly affected by heavy metals. Moreover, no significant differences in metal concentrations existed between the dry and wet seasons. A strong positive correlation occurred between Zn and Fe only during the wet season. Water from the river was polluted with Fe and unsuitable for domestic use. Potential sources of contamination include agricultural areas, industrial effluents, and domestic waste in the wet season, and industrial and domestic sewage in the dry season. To make the river water safe for use, it should be treated and regularly monitored for metal contents, and sources of contamination should be managed appropriately.